Status Gizi Lebih dan Asupan Natrium Tinggi Meningkatkan Risiko Hipertensi pada Remaja: Studi Kasus-Kontrol di Perkotaan: Overweight and High Sodium Intake Increased Risk of Hypertension among Adolescents: A Case-Control Study in Urban Setting - Rifka Annisa Aura Nuradina; Widya Asih Lestari; Imas Arumsari (Amerta Nutrition, 2023)
Background: Hypertension is the leading risk factor for cardiovascular disease development. Although hypertension in adults and the elderly is more common, adolescent hypertension has increased in the past two decades. Hypertension at an early age affects cognitive performance and increases the risk of cardiovascular diseases and premature death in the future. The risk factors of hypertension are often related to urban populations' unhealthy lifestyles. Objectives: To investigate the risk factors of hypertension among urban adolescents. Methods: This case-control study matched by age and sex was conducted between January – July 2021 in Tangerang City, Indonesia, involving 66 adolescents. Blood pressure was measured two times using Omron® automated sphygmomanometer. The BMI defines nutritional status for age. High-sodium food sources, fruit and vegetable, and coffee consumption were assessed using an SQ-FFQ. The statistical analysis used was a Chi-square test (95% CI). Results: The results show there is a significant relationship between nutritional status [p=0.001, OR (95%CI)= 6.133 (2.111 – 17.824)] and high-sodium food source consumption [p=0.001, OR(95%CI)= 6.824 (1.958 – 23.782)] with hypertension. There is no significant relationship between coffee [p=0.613, OR (95%CI)= 3,200 (0,315 – 32,475)], fruit [p=0.071, OR(95%CI)= 2.604(0.911– 7.445)] and vegetable [p= 0.125, OR(95%CI)= 2.222(0.795 – 6.211)] consumption with hypertension. Conclusions: Overweight and sodium consumption increases the risk of adolescent hypertension. These factors can be modified and improved by increasing a healthy lifestyle, mainly in the urban. Future strategic interventions addressing adolescents' unhealthy lifestyles (high consumption of fat, sodium, sugar, and low physical activity) should be considered.